Lifestyle factors and determination of optimal cut-off values for forward head posture in young adults with neck pain: a cross-sectional analysis - Jaeho Lee; Kyoungsik Jeong; Sujeong Mun; Siwoo Lee; Younghwa Baek (BMC Musculoskeletal Disorders)
Abstract Background Neck pain is a common condition across various populations, with a substantial impact on daily life and quality of life. Forward head posture is frequently observed in individuals with neck pain and is closely associated with lifestyle factors. This study aimed to examine the relationship between lifestyle factors and forward head posture in young adults with neck pain and determine the optimal cutoff value for assessing the risk of forward head posture. Methods In total, 200 men and women aged 35–44 years with persistent or recurrent neck pain with a numeric rating scale score of ≥ 3 in the previous week were included in the study. The participants’ sex, age, medical history, anthropometric parameters, posture- and activity-related lifestyle, pain, radiographs, and the craniovertebral angle were obtained. The associations between lifestyle factors and forward head posture were analyzed using logistic regression. The cutoff values for risk prediction were analyzed using receiver operating characteristic curves. The impact of lifestyle factors on changes in craniovertebral angle at the 6-month follow-up was analyzed using multiple linear regression and analysis of covariance. Results After adjusting for covariates, there were significant differences in lying time (odds ratio = 3.342, 95% confidence interval = 1.607–6.952) and physical activity level index (odds ratio = 0.404, 95% confidence interval = 0.210–0.775) between the forward and non-forward head posture groups. The cutoff values for detecting forward head posture were 6.50 h of lying time and a physical activity level score of 2.88. At the 6-month follow-up, the craniovertebral angle was closer to the diagnosis of forward head posture, with increasing lying time and lower physical activity level score; however, the association was not statistically significant. Conclusions The findings indicate that lying time and physical activity level scores are important lifestyle-related predictors of forward head posture. Thus, lying time and physical activity level should be addressed to predict and prevent forward head posture.